2008
DOI: 10.1097/dad.0b013e31815b8ed5
|View full text |Cite
|
Sign up to set email alerts
|

CD117 Immunoreactivity in Atypical Fibroxanthoma

Abstract: Atypical fibroxanthoma (AFX) is a spindle cell neoplasm of the skin seen typically on sun-damaged skin of the elderly. Though described as a benign entity, local recurrence and distant metastasis have been reported. This study aims to investigate the potential pathogenic role of CD117, the c-kit receptor in AFX. CD117 was detected in 15 of the 16 cases (94%). The percentage of positive cells for CD117 expression among all tumors was approximately 30%. CD117 proved to be a very sensitive marker of AFX. This ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Along similar lines, we did note scattered positive CD 117 cells, but these appeared to be in the smaller dendritic cells and we did not interpret this as positive staining. CD117 has been reported to be potentially helpful in identifying AFXs as they have been reported in 15 of 16 AFXs studied 35 . However, in their study, Mathew et al, demonstrated bland CD117 positive dendritic appearing cells with surrounding atypical tumor cells unstained, in their photomicrographs.…”
Section: Discussionmentioning
confidence: 82%
“…Along similar lines, we did note scattered positive CD 117 cells, but these appeared to be in the smaller dendritic cells and we did not interpret this as positive staining. CD117 has been reported to be potentially helpful in identifying AFXs as they have been reported in 15 of 16 AFXs studied 35 . However, in their study, Mathew et al, demonstrated bland CD117 positive dendritic appearing cells with surrounding atypical tumor cells unstained, in their photomicrographs.…”
Section: Discussionmentioning
confidence: 82%
“…In our immunohistochemical study tumoral cells were diffusely stained with vimentin, CD10, CD68, CD99, a-1-antitrypsin, and isolated cells for c-kit. Recently, CD99, CD10 and c-kit were described as sensitive markers of classic AFX [16,17,18]. However, these antibodies have not been studied in most of the published CCAFXA.…”
Section: Discussionmentioning
confidence: 99%
“…5,[31][32][33][34][35][36][37][38][39] The current role of immunostains for diagnosis of MFH/UPS is largely to assist in ruling out common mimics, although it is likely that novel stains will serve as more specific markers in the future (Fig 4). At the present time, utilization of a panel including S-100, cytokeratin stains, and smooth muscle actin is helpful in differentiating MFH from desmoplastic melanoma, spindle cell squamous cell carcinoma, and leiomyosarcoma, respectively.…”
Section: Immunohistochemistrymentioning
confidence: 99%